Prototype Monitoring Suhu Dan Kelembapan Pada Ruang Server Di RSU PKU Muhammadiyah Sragen Berbasis Internet Of Things - Aldita Kusuma Wardana; Rudi Susanto; Pramono Pramono (SMATIKA JURNAL : STIKI Informatika Jurnal, 2025)
The Internet of Things (IoT) is an embedded system designed to expand the utilization of always-active internet connectivity. IoT infrastructure includes existing networks and the internet along with its evolution. This infrastructure supports the process of object identification, sensors, and connectivity capabilities, serving as the foundation for the development of independent cooperative services and applications. IoT is also characterized by a high level of autonomy in data collection, event transfer, network connectivity, and interoperability. A microcontroller is a computer system on a single IC chip, often referred to as a single-chip microcomputer. With the advancement of microcontrollers, IoT has evolved to include modern Ethernet- and Wi-Fi-based modules, one of which is the ESP8266. This research aims to develop a temperature and humidity monitoring system for the server room at RSU PKU Muhammadiyah Sragen based on the Internet of Things. With this system, the temperature and humidity in the server room can be monitored online from anywhere, enabling quick action to be taken in the event of excessive temperature rise. The research method involves several stages, including data collection, needs analysis, design, planning, and testing. The results of this study indicate that the developed design is capable of detecting temperature and humidity in the RSU PKU Muhammadiyah Sragen server room, and this information can be displayed through the Blynk application. The testing of the server room monitoring system shows that the temperature sensor has an accuracy of 92.0%, while the humidity sensor shows a value of 91.03 %.